2017
DOI: 10.1016/j.ymgmr.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Isovaleric acidemia: Therapeutic response to supplementation with glycine, l -carnitine, or both in combination and a 10-year follow-up case study

Abstract: Isovaleric acidemia (IVA) is an organic acid disease caused by a deficiency of isovaleryl-CoA dehydrogenase. Deficiency of this enzyme leads to accumulation of organic acids, such as isovalerylcarnitine and isovalerylglycine. The proposed IVA treatments include leucine restriction and l-carnitine and/or glycine supplementation, which convert isovaleric acid into non-toxic isovalerylcarnitine and isovalerylglycine, respectively. We examined the therapeutic response using the leucine load test and performed a 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
(25 reference statements)
1
21
0
Order By: Relevance
“…In accordance with the findings of this study, hypothyroidism was reported to be a risk factor for diabetes mellitus (32), while TSH level was associated with and increased risk of GDM (33). Isovaleric academia is an inborn error of metabolism, characterized by a deficiency of isovaleryl-CoA dehydrogenase, leading to accumulation of isovalerylcarnitine or isovaleryglycine (34). Methylmalonic aciduria is another inborn error of metabolism, characterized by a deficiency of the enzyme methylmalonyl-CoA mutase (35).…”
Section: Discussionsupporting
confidence: 86%
“…In accordance with the findings of this study, hypothyroidism was reported to be a risk factor for diabetes mellitus (32), while TSH level was associated with and increased risk of GDM (33). Isovaleric academia is an inborn error of metabolism, characterized by a deficiency of isovaleryl-CoA dehydrogenase, leading to accumulation of isovalerylcarnitine or isovaleryglycine (34). Methylmalonic aciduria is another inborn error of metabolism, characterized by a deficiency of the enzyme methylmalonyl-CoA mutase (35).…”
Section: Discussionsupporting
confidence: 86%
“…54 Accumulations of 3-hydroxyisovalerylcarnitine and isovalerylcarnitine in higher concentrations are associated with metabolic deficiency in leucine metabolism and with protein absorption from foods. [55][56][57] Lower folate concentrations in the serum are linked to abnormal functioning of the proximal small intestinal mucosa, which can reduce folate absorption. 58 Tissue damage and alterations in the host metabolism can significantly change the shortchain acylcarnitines, amino acids in the plasma, and other metabolic profiles in canines with IBD.…”
Section: Canine Gut Microbiota and Gi Diseasesmentioning
confidence: 99%
“…Furthermore, they present similar clinical symptoms, such as poor feeding, poor growth, delayed development, and intellectual disorders [50,51]. Newborns with Isovaleric acidemia were treated with low Leucine diet and supplement with l-carnitine and Glycine [52,53], and neonates with 2-MBG were suggested to be treated with avoidance of fasting, protein restriction and carnitine supplementation [54]. Since preterm neonates are not affected with IVA or 2-MBG, supplement with l-carnitine, BCAAs and Glycine may be beneficial for growth and development of preterm neonates who have a low ratio of (Leucine + Isoleucine + Proline-OH) to C5.…”
Section: Performance Of the Final Newborn Metabolic Model For Identifmentioning
confidence: 99%